Eliciting Utility Curvature in Time Preference - Stephen L. Cheung (Institute of Labor Economics (IZA), 2019)
This paper examines the effects of alternative assumptions regarding the curvature of utility upon estimated discount rates in experimental data. To do so, it introduces a novel design to elicit time preference building upon a translation of the Holt and Laury method for risk. The results demonstrate that utility elicited directly from choice over time is significantly concave, but far closer to linear than utility elicited under risk. As a result, the effect of adjusting discount rates for this curvature is modest compared to assuming linear utility, and considerably less than when utility from a risk preference task is imposed.
Keywords: C91; D01; D90; 330; time preference; measurement of utility; discounted utility; choice list